УМОВИ ЕФЕКТИВНОГО ФОРМУВАННЯ КОМУНІКАТИВНОЇ КУЛЬТУРИ СТУДЕНТІВ ЗАСОБАМИ ПОЗААУДИТОРНОЇ РОБОТИ (Педагогіка вищої та середньої школи, 2009)
The article deals with the problem of pedagogical conditions of effective forming students' communicative culture by means of extracurricular activity in higher pedagogical school.